Effects of contradictory nutrition information on intention to change behaviour : the role of attitude extremity and attitude certainty - Tan, Hui Xin (2018)
This study examines the relationship between contradictory nutrition information and its effects on intention to change food consumption behaviours. Through a within-subjects, posttest only experimental study conducted among Singaporeans living in Housing Development Blocks (HDB) (N = 369), we tested our hypotheses by exposing participants to three experimental conditions: only positive information, only negative information, and both positive and negative information. Stimuli were developed based on the results of a pilot study (N = 101). Overall, the experiment confirmed that exposure to contradictory information led to less extreme attitudes and lower intentions to change behaviour. In addition, exposure to contradictory information did not lead to the highest attitude certainty among the three conditions as hypothesized. Finally, attitude certainty did have a moderating effect on the relationship between attitude extremity and intention to change behaviour, but only for the mixed information condition.